2006
DOI: 10.4269/ajtmh.2006.75.273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Variability in the Occurrence of Leishmaniasis in Northeastern Colombia

Abstract: Previous studies have shown that variation in the distribution of vectors associated to the transmission of Leishmania species may be related to climatic changes. However, the potential implications of these ecological changes in human health need to be further defined in various endemic populations where leishmaniasis carries a substantial burden of disease such as in Northeastern Colombia. Herein, we report the impact of El Niño Southern Oscillation climatic fluctuations during 1985-2002 in the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 18 publications
7
84
2
7
Order By: Relevance
“…On average, Leishmania infections increased 2 months after a relative decrease in rainfall and this correlation followed the same direction at the annual scale: dry years were years where infection numbers were greater. Cardenas and others 15 showed that, in Columbia, during El Niñ o episodes leishmaniasis increased, whereas during La Niñ a periods it decreased; this is similar to the present observation. Chaves and others 3 using time series analysis showed that it was possible to accurately predict leishmaniasis incidence dynamics up to 12 months before the incidence.…”
Section: Discussionsupporting
confidence: 81%
“…On average, Leishmania infections increased 2 months after a relative decrease in rainfall and this correlation followed the same direction at the annual scale: dry years were years where infection numbers were greater. Cardenas and others 15 showed that, in Columbia, during El Niñ o episodes leishmaniasis increased, whereas during La Niñ a periods it decreased; this is similar to the present observation. Chaves and others 3 using time series analysis showed that it was possible to accurately predict leishmaniasis incidence dynamics up to 12 months before the incidence.…”
Section: Discussionsupporting
confidence: 81%
“…At the end of this period, the rate of calved females and natural Leishmania infections has also been determined to be signiicantly higher. In the area of Urabá during the phenomenon "El Niño" a tendency towards decreased vectors has been identiied, contrary to what was reported by Cardenas et al [62].…”
Section: Contributions To the Knowledge Of Phlebotominescontrasting
confidence: 53%
“…During that period, it was identified that during El Niño, cases of leishmaniasis increased up to 15.7% in disease incidence in North Santander and 7.74% in Santander, whereas during La Niña phases, leishmaniasis cases decreased 12.3% in Santander and 6.8% in North Santander. When mean annual leishmaniasis cases were compared between La Niña and El Niño years, significant differences were found for North Santander (p<0.05) but not for Santander (p=0.05) (Cárdenas et al, 2006). During the same study period in southern provinces, effects of climate variability and change were also studied regarding leishmaniasis incidences.…”
Section: Evidences Regarding Climate Change and Its Potential Effect mentioning
confidence: 99%
“…Although many studies may have some limitations, such as a lack of incorporation of other meteorological factors into the analysis (temperature, rainfall, sun radiation, transpiration or evotranspiration, relative humidity, vegetation indexes [Normalized Difference Vegetation Index, NDVI and Enhanced Vegetation Index, EVI] among others) (Cárdenas et al, 2006), it has been suggested that such findings are relevant from a public health perspective to better understand the ecoepidemiology of different communicable diseases (Rodriguez-Morales, 2005). However, further research is needed in this region and other endemic areas to develop monitoring systems that will assist in predicting the impact of climate changes in the incidence of tropical diseases in endemic areas with various biological and social conditions.…”
Section: Climate Change and Communicable Diseases: Public Health Persmentioning
confidence: 99%